Plasma-Reactor Wall Interactions: Bromine-Fluorine Chemistry Duality in an Industrial Dry Etch Process. Issue 1803 (11th June 2015) - Rizquez, M.; Roussy, A.; Bortoloti, B.; Pinaton, J.; Goasduff, Y.
ABSTRACT: The purpose of the present paper is to investigate the composition of the coating formed on the plasma reactor walls after an industrial process which is divided into two steps, where the chemistries used are CF4 /CH2 F2 followed by HBr/O2 . Since Fluorine traces have been detected through the plasma and over the wafer even during the second chemistry, investigations of the Br-F chemistry duality for a new silicon etching process have been performed in order to see the reactions which are taking place inside of the reactor. The understanding of these formations is really important to avoid process instabilities and get better performance of the transistors. The coating on the walls after the process and after the cleaning between wafers has been characterized in order to figure out the level of F traces after each step and to understand the reminiscence of this element over time. This study is the starting point to propose a modification on the Waferless AutoClean (WAC) used nowadays in an industrial process.